2020
DOI: 10.3390/jcm9103190
|View full text |Cite
|
Sign up to set email alerts
|

Onlay Uncemented Lateralized Reverse Shoulder Arthroplasty for Fracture Sequelae Type 1 with Valgus/Varus Malunion: Deltoid Lengthening and Outcomes

Abstract: The successful treatment of proximal humeral fractures remains challenging for shoulder surgeons, and failure rates are high, regardless of initial treatment. This study aimed to analyze the clinical and radiographic midterm results of onlay lateralized cementless stem reverse shoulder arthroplasty (RSA) in patients with valgus/varus malunion proximal humerus fracture sequelae without metaphyseal osteotomy. We retrospectively studied 35 cases with the diagnosis of fracture sequelae of the proximal part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Biomechanically, lack of compressive forces between the glenosphere and humeral socket are the main parameters associated with instability, consequent to a loss of tension of the deltoid and the remaining cuff associated with proximal bone resorption in late dislocations. Small glenoid size, the deltopectoral approach, poor subscapularis muscle condition, revision surgery, younger male patients, association with scapular notching, resorbed tuberosities/proximal bone loss, and inadequate humeral length or version were all reported to be factors relating to higher rates of instability [ 11 , 22 , 65 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanically, lack of compressive forces between the glenosphere and humeral socket are the main parameters associated with instability, consequent to a loss of tension of the deltoid and the remaining cuff associated with proximal bone resorption in late dislocations. Small glenoid size, the deltopectoral approach, poor subscapularis muscle condition, revision surgery, younger male patients, association with scapular notching, resorbed tuberosities/proximal bone loss, and inadequate humeral length or version were all reported to be factors relating to higher rates of instability [ 11 , 22 , 65 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…[26] Since the publication of a study by Ascione et al showing an increased prevalence of scapular spine fractures after RSA with an onlay-design (i.e. with additional lengthening of the arm due to a humeral onlay polyethylene component) everybody should be aware of the risks of overlengthening the arm [27].…”
Section: Discussionmentioning
confidence: 99%
“…Scapular notching was the most frequently reported problem after the analyzed RSA, even though it did Nevertheless, scapular notching remains a concern of relevance certain etiologies, such as fracture sequelae [57]. Grubhofer et al [33] studied 44 shoulders operated on after failed osteosynthesis of proximal humeral fractures; 41 out of 44 cases (93%) were affected by scapular notching, and it was the only study that reported a stage 4 notching (4 cases).…”
Section: Discussionmentioning
confidence: 99%